2012
DOI: 10.1097/bor.0b013e32835059cd
|View full text |Cite
|
Sign up to set email alerts
|

Drug-induced rheumatic diseases

Abstract: It is important to recognise that drugs used in other specialties may induce rheumatic disease and vigilance on making a diagnosis is the key.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Among newer medications that can cause vasculitis, special attention is paid to TNF inhibitors and new small molecules, i.e. kinase inhibitors: gefitinib used in oncology and masitinib, analyzed in terms of the treatment effectiveness in rheumatoid arthritis [2, 3]. …”
Section: Drug-induced Vasculitismentioning
confidence: 99%
See 4 more Smart Citations
“…Among newer medications that can cause vasculitis, special attention is paid to TNF inhibitors and new small molecules, i.e. kinase inhibitors: gefitinib used in oncology and masitinib, analyzed in terms of the treatment effectiveness in rheumatoid arthritis [2, 3]. …”
Section: Drug-induced Vasculitismentioning
confidence: 99%
“…The most frequently mentioned drugs are TNF inhibitors including etanercept and adalimumab. These drugs cause full-blown disease with the occurrence of anti-Jo-1 antibodies, but there is also a case of a patient with clinical symptoms without the presence of antibodies in serum [2, 12]. Liu et al [13] presented a case of a 46-year-old patient who reported DM symptoms after etanercept administration.…”
Section: Drug-induced Polymyositis and Dermatomyositismentioning
confidence: 99%
See 3 more Smart Citations